1994
DOI: 10.1093/ajcn/60.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a low-insulin-response, energy-restricted diet on weight loss and plasma insulin concentrations in hyperinsulinemic obese females

Abstract: The effects of two low-energy diets on serum insulin concentrations and weight loss in obese hyperinsulinemic females were compared during a 12-wk period. The first diet (n = 15) was designed to evoke a low insulin response (ID), and the second (n = 15) was a conventionally balanced diet (ND). After a 12-wk washout period, seven and nine subjects who had been on the ID and ND, respectively, changed to the alternative diet for 12 wk. Variables studied were basal and 30- and 120-min concentrations of blood gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
101
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(108 citation statements)
references
References 30 publications
5
101
0
2
Order By: Relevance
“…Similar findings have been reported in patients with type II diabetes in whom LGI diets lowered fasting total cholesterol, very low-density lipoprotein (VLDL) concentrations and increased HDL concentrations and reduced PAI levels (Jarvi et al, 1999). In addition, LGI has been shown prospectively to have additional short-term benefits (Frost et al, 1994), improving clotting parameters by suppressing plasminogen activator inhibitor compound-1 (Jarvi et al, 1999), reducing blood pressure (Sciarrone et al, 1993) and inducing weight loss (Slabber et al, 1994). Also in a group of people who were hyperlipidaemic, the addition of low-glycaemic diet to the standard healthy eating advice produced a significant decrease in total cholesterol and TG concentrations.…”
Section: Introductionsupporting
confidence: 62%
“…Similar findings have been reported in patients with type II diabetes in whom LGI diets lowered fasting total cholesterol, very low-density lipoprotein (VLDL) concentrations and increased HDL concentrations and reduced PAI levels (Jarvi et al, 1999). In addition, LGI has been shown prospectively to have additional short-term benefits (Frost et al, 1994), improving clotting parameters by suppressing plasminogen activator inhibitor compound-1 (Jarvi et al, 1999), reducing blood pressure (Sciarrone et al, 1993) and inducing weight loss (Slabber et al, 1994). Also in a group of people who were hyperlipidaemic, the addition of low-glycaemic diet to the standard healthy eating advice produced a significant decrease in total cholesterol and TG concentrations.…”
Section: Introductionsupporting
confidence: 62%
“…Short-term studies in humans showed lower satiety, increased hunger or higher voluntary food intake in subjects consuming high compared to low GI meals (Ludwig, 2002;Roberts et al, 2002). Weight loss in obese hyperinsulinaemic women was higher in those consuming an energy restricted low compared to high glycaemic diet for 12 weeks (Slabber et al, 1994), and in men lower adiposity was found after consumption of an energy-restricted low glycaemic diet for 5 weeks (Bouche et al, 2002). Although these were all shortterm findings in mostly obese subjects, this mechanism may play a role in normal subjects to maintain normal weight over a longer period.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have indicated that carbohydrates and the GI values of meals can play a role in promoting weight gain and obesity (Slabber et al, 1994;Ludwig et al, 1999;Bessesen, 2001;Anderson et al, 2002). A low-GI diet has been advocated for the treatment and prevention of overweight and obesity in the general public in the US (Ludwig, 2000;Ebbeling, 2001;Pawlak et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the benefits of dietary fat restriction on weight management have been only modest (Astrup et al, 2000). Some studies have focused on the role of other dietary factors, such as carbohydrates and the GI values of meals, in promoting or preventing weight gain and obesity (Slabber et al, 1994;Ludwig et al, 1999;Bessesen, 2001). The slower digestion of carbohydrates with low-GI values has been found to be associated with higher satiety (Holt et al, 1992), improved insulin sensitivity (Frost et al, 1999) and other beneficial metabolic effects (Jenkins et al, 1987).…”
Section: Introductionmentioning
confidence: 99%